The Growth Penalty of High Government Pay Rates - Craig Sugden; Kiyoshi Taniguchi (Asian Development Bank (ADB), 2008)
This study examines the role of government pay rates in economic growth. A trend decline in government pay rates, expressed relative to what an economy can afford, is identified in many developing countries. The decline is attributed to the erosion of economic rents. Drawing on the theoretical insights of the Harris- Todaro two sector model, the study argues that static and dynamic benefits from the erosion of rents would lead to a negative relationship between government pay rates and economic growth. Utilizing the pooled regression models as well as the feasible two-stage generalized method of moments estimator, the study concludes that relative government pay rates are negatively related with economic growth in developing countries; hence, high government pay rates penalize economic growth. Countries that retain high government pay rates are identified.
hdl:11540/1773
Keywords: 330; Staatsquote; Vergütungssystem im öffentlichen Dienst; Wirtschaftswachstum